Postnatal maturation of the opioid and endocannabinoid signalling systems within the descending pain pathway of the rat - Kwok, C. (2015)
Significant opioid- and endocannabinoid-dependent changes occur within the periaqueductal grey (PAG), rostroventral medulla (RVM) and spinal cord (DH) during postnatal development of the rat (Sprague Dawley). These changes are involved in the differential descending control of spinal excitability between young and mature rats. Microinjection of the µ-opioid receptor (MOR) agonist DAMGO (30ng) into the PAG of rats increased spinal excitability and lowered mechanical threshold to noxious stimuli in postnatal day (P)21 rats, but had inhibitory effects in adults and lacked efficacy in P10 pups. A tonic opioidergic tone within the PAG was revealed in adult rats by intra-PAG microinjection of CTOP (120ng, MOR antagonist) which lowered mechanical thresholds and increased spinal reflex excitability. Spinal adminstration of DAMGO inhibited spinal excitability in all ages yet the magnitude of this was greater in younger animals than in adults. The expression of MOR and related peptides were also investigated using TaqMan RT-PCR and immunohistochemistry. Proopiomelanocortin (POMC) peaked at P21 in the ventral-PAG, and MOR increased significantly in the DH as the animals aged. CB1/CB2 receptor activation by WIN55212 (4µg, CB1/CB2 agonist) and HU210 (4µg, CB1/CB2 receptor agonist) in the PAG, RVM and DH was anti-nociceptive in both young (P10, P21) and adult rats, but GPR55 receptor activation by LPI (12µg, endogenous GPR55 agonist) and AM251 (2.77µg, CB1 antagonist, GPR55 agonist) was exclusively inhibitory in young rats. Micro-injection of LPI into the adult RVM facilitated spinal reflex excitability, suggesting that GPR55 receptor activation in mature animals is pro-nociceptive. The expression of cannabinoid receptors and endocannabinoid-synthesising enzymes was investigated with immunohistochemical and TaqMan RT-PCR techniques. Overall the expression of CB1 receptors and the anandamide synthesising enzyme NAPE-phospholipase D (NAPE-PLD) increased within the descending pain pathway with age, whereas the expression of the 2-AG synthesising enzyme Diacylglycerol lipase α (DAGLα) decreased. These results illustrate that profound differences in the endogenous-opioidergic and endocannabinoid signalling systems occur within the descending pain pathway throughout postnatal development.